2014
DOI: 10.1002/jssc.201300927
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and rapid determination of elemental nanosulfur/sulfur by liquid chromatography

Abstract: In order to identify the most suitable method for the estimation of nanosulfur for studying its residue dynamics, the present work was taken up. HPLC and GC methods were explored for its analysis. A comparative study of the existing analytical methods for the quality control of nanosulfur was undertaken. UV spectrophotometry and HPLC methods were superior with lower LOD when compared to GC-MS, which was not satisfactory due to breakage of catenated S20 into S6 and S8 . The method has been validated by analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…43 As in studies previously discussed, 22,39 the authors found multiple peaks for GC-MS in standard solutions, where there was a large S 8 peak, a smaller (by almost one-third) S 6 peak and many peaks of other S allotropes, leading to its relatively high LOD. 43 HPLC, therefore, was found to be the better tool owing to its high sensitivity and selectivity compared with GC-MS and UV spectrophotometry. UV spectrophotometry may lead to a higher estimated sulfur content on account of its inability to be selective between organic and inorganic sulfur at the wavelength used.…”
Section: Chromatographymentioning
confidence: 73%
See 4 more Smart Citations
“…43 As in studies previously discussed, 22,39 the authors found multiple peaks for GC-MS in standard solutions, where there was a large S 8 peak, a smaller (by almost one-third) S 6 peak and many peaks of other S allotropes, leading to its relatively high LOD. 43 HPLC, therefore, was found to be the better tool owing to its high sensitivity and selectivity compared with GC-MS and UV spectrophotometry. UV spectrophotometry may lead to a higher estimated sulfur content on account of its inability to be selective between organic and inorganic sulfur at the wavelength used.…”
Section: Chromatographymentioning
confidence: 73%
“…HPLC, therefore, was found to be the better tool owing to its high sensitivity and selectivity compared with GC‐MS and UV spectrophotometry. UV spectrophotometry may lead to a higher estimated sulfur content on account of its inability to be selective between organic and inorganic sulfur at the wavelength used . Figure shows the LC‐MS/MS mass spectra of a nanosulfur formulation with a parent ion peak at m / z 989.3 which implied about 30 S catenated together .…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations